Bilateral spontaneous pneumothorax- A late complication of COVID-19 infection- case report and review of literature - Balasundaram, Sandhya; Sutrave, Sumeeth (Indian Journal of Case Reports, 2026)
We report a case of bilateral spontaneous pneumothorax in a 32-year-old non-smoker male. The patient presented to the emergency department with complaints of sudden-onset left-sided chest pain and breathlessness. A chest X-ray was taken, which revealed a left pneumothorax. Immediately, left-sided intercostal chest drain was placed. The patient gave a history of similar complaints 1 week back and was diagnosed with right-sided pneumothorax, for which right-sided chest drain was placed in an outside hospital. The patient was a non-smoker and had no comorbidities. He reported having a COVID-19 infection 1 month back, which was treated symptomatically under home quarantine, not requiring any hospitalization or supplemental oxygen. After 1 week of placement of chest drain, as air leak persisted, a computed tomography-chest was done, which revealed a left mild hydropneumothorax and communication with the apical segment and pleural cavity suggestive of bronchopleural fistula. The right lung had expanded. After ruling out secondary infection, the patient was referred to cardiothoracic surgery for decortication and surgical closure of the bronchopleural fistula. The patient recovered with no complications in the post-operative period. Spontaneous pneumothorax in post-COVID patients can happen as a late complication, which requires high clinical suspicion and vigilance for timely diagnosis and treatment.